1996
DOI: 10.1046/j.1365-2249.1996.907600.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized immune activation in pulmonary tuberculosis: co-activation with HIV infection

Abstract: Parameters of immune activation/differentiation were studied in a group of newly diagnosed HIV− and HIV+ pulmonary tuberculosis (TB) patients. Compared with controls, HLA‐DR expression on both CD4 and CD8 T cells from the HIV− TB patients was approximately doubled; HLA‐DR on T cells from the HIV+ group was tripled. The monocytes from both groups of patients expressed abnormally high levels of the Fcγ receptors I and III. Serum levels of tumour necrosis factor‐alpha (TNF‐α), neopterin and β2‐microglobulin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 36 publications
14
94
1
2
Order By: Relevance
“…Together, the modulation of these factors may be responsible for a bystander effect that allows M. tuberculosis to subvert the differentiation of monocytes into dendritic cells that are deficient in priming naïve T cells and, instead, contribute to pathogenic dissemination (Mariotti et al 2002;Skold and Behar 2008;Rajashree et al 2009). This premise is in line with the imbalance in the relative proportions of blood-circulating monocytes observed in tuberculosis patients, in which the abundance of the CD14 þ CD16 þ subset is accentuated and shown to have a defective differentiation program toward functional dendritic cells (Vanham et al 1996;Balboa et al 2013). In the case of IL-10, it was shown to be part of the bystander effect induced by M. tuberculosis to inhibit the differentiation of human monocytes into CD1c þ DCs, suggesting it plays an important role in the recruitment of dendritic cell precursors that may be incapable to activate efficiently the adaptive immune response (Remoli et al 2011).…”
Section: Dendritic Cell Differentiation and Activation: Manipulation supporting
confidence: 65%
“…Together, the modulation of these factors may be responsible for a bystander effect that allows M. tuberculosis to subvert the differentiation of monocytes into dendritic cells that are deficient in priming naïve T cells and, instead, contribute to pathogenic dissemination (Mariotti et al 2002;Skold and Behar 2008;Rajashree et al 2009). This premise is in line with the imbalance in the relative proportions of blood-circulating monocytes observed in tuberculosis patients, in which the abundance of the CD14 þ CD16 þ subset is accentuated and shown to have a defective differentiation program toward functional dendritic cells (Vanham et al 1996;Balboa et al 2013). In the case of IL-10, it was shown to be part of the bystander effect induced by M. tuberculosis to inhibit the differentiation of human monocytes into CD1c þ DCs, suggesting it plays an important role in the recruitment of dendritic cell precursors that may be incapable to activate efficiently the adaptive immune response (Remoli et al 2011).…”
Section: Dendritic Cell Differentiation and Activation: Manipulation supporting
confidence: 65%
“…Interestingly, since IL-1β has been described as an IL-12-inducing agent on human , the reduction of IL-1β + cells observed in CD16 + Mo-DCs could be associated with the low levels of IL-12 + cells. As TB patients have a high percentage of circulating CD16 + Mos [11,12], this dichotomy in the differentiation fate of Mo subsets can explain the impairment observed in Mo-derived DCs from TB patients [21]. In addition, we observed that CD16 + depletion in Mos from TB patients improved the differentiation toward DCs and that the addition of CD16 + Mos impaired the differentiation of Mos from HSs.…”
Section: Discussionmentioning
confidence: 61%
“…We have previously demonstrated that Mos from healthy subjects (HSs) exposed to IL-4 and GM-CSF generate mainly CD1a + CD14 − DC-SIGN high CD86 low DCs, which are efficient APCs for Mtb-specific T cells, while Mos from TB patients fail to differentiate into DCs generating a CD1a − CD14 + DC-SIGN low CD86 high cell population [21], which induces a low specific T-cell proliferation in response to Mtb [26]. Moreover, it has been demonstrated that the circulating CD16 + Mo subset is increased in TB patients [11,12].In this study, we evaluated whether the imbalance in the relative proportion of the Mo subsets in TB patients could explain the altered differentiation toward DCs in terms of CD1 molecules and DC-SIGN expression. Our results show that altered CD1a − DC-SIGN low DCs are generated from CD16 + Mos, which are enriched in TB patients, involving a sustained p38 MAPK activity during their differentiation process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our work, as well as that of others, downplays the role of mycobacteria-induced soluble factors or NF-kBdependent transcriptional activation in upregulating HIV expression (Shattock et al, 1993;, Dezzutti et al, 1999Ghassemi et al, 2000). Other studies, while reporting an enhancement of HIV p24/RT levels accompanied by cytokine secretion or cytokine-mediated NF-kB-dependent transcriptional activation, did not demonstrate fully a link between these events (Zhang et al, 1995;Goletti et al, 1996Goletti et al, , 1998Vanham et al, 1996). Mancino et al (1997) have reported that viable but not heat-killed M. tuberculosis mediated an increase in HIV production in monocyte-derived macrophages, while Dezzutti et al (1999) have shown that heat-killed and viable MAC enhanced the replication of lymphocytotropic HIV-1 strain LAI in CD8-depleted PBMCs to comparable levels.…”
Section: Discussionmentioning
confidence: 98%